Usefulness of Lumbar Puncture During the First Febrile Seizure in Children; A Series of 182 Patients - Abidi, K.; Lahmini, W.; Bourrouss, M. (British Journal of Healthcare and Medical Research, 2023)
Purpose: Our study's objectives are to describe the epidemiological, clinical, paraclinical, etiological evolutionary aspects of febrile seizures (FS) in children, as well as to evaluate the contribution of lumbar puncture (LP) in FS in children. Methods: Our research includes a cross-sectional review of all children admitted for a febrile seizure and whose age is between 6 months and 5 years. A retrospective study carried out in the pediatric emergency department at university hospital center Mohammed VI over the period from 2020 to 2022; in this period 182 patients were admitted. Results: FS accounted for 4.37% of emergency hospitalizations, with a peak in frequency during the winter. The average age was 18 months. The majority of hospitalized children were from a low socioeconomic level (71.5%). The temperature on admission was between 38.5 and 39.4°C in 44.5% of cases. Simple FS were the most frequent (69.8%). The LP made in all patients was always normal. Gastroenteritis and respiratory infections were the most frequent etiologies of fever. Etiological treatment was also instituted for patients according to the etiology. The evolution was marked by the improvement of the patients. No deaths have been reported Conclusion: The likelihood of bacterial meningitis or encephalitis in uncomplicated FS without any other signs is extremely low, regardless of the age of the child. In front of a simple FS without any evocative sign of meningitis or encephalitis, the LP is not necessary, even before 18 months